2021
DOI: 10.1038/s42003-021-01954-0
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro tumorigenesis model based on live-cell-generated oxygen and nutrient gradients

Abstract: The tumor microenvironment (TME) is multi-cellular, spatially heterogenous, and contains cell-generated gradients of soluble molecules. Current cell-based model systems lack this complexity or are difficult to interrogate microscopically. We present a 2D live-cell chamber that approximates the TME and demonstrate that breast cancer cells and macrophages generate hypoxic and nutrient gradients, self-organize, and have spatially varying phenotypes along the gradients, leading to new insights into tumorigenesis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Our earlier work has shown that murine 4T1 tumor cells can express high Nos2 and Cox2 levels and that Nos2/Cox2 blockade limited tumor growth [ 16 , 17 ]. Thus, 4T1 tumor bearing mice are representative of NOS2 Hi /COX2 Hi breast tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier work has shown that murine 4T1 tumor cells can express high Nos2 and Cox2 levels and that Nos2/Cox2 blockade limited tumor growth [ 16 , 17 ]. Thus, 4T1 tumor bearing mice are representative of NOS2 Hi /COX2 Hi breast tumors.…”
Section: Resultsmentioning
confidence: 99%
“…This allows us to distinguish between viable and nonviable cells within a heterogeneous cancer cell population. It provides quantitative data and allows us to for investigate various aspects of cancer cell behavior, which can have significant implications for cancer therapy and drug development. − After 24 h of incubation with CAAT NPs, 4T1 cells are stained with FDA/PI and examined under a fluorescence microscope. There was no significant cell death in the untreated and AAT control groups.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of directly comparing HIF1α staining and ImageIT probe staining, a few studies in the literature in the field of oncology have compared the spatial localization of the ImageIT hypoxia probe and HIF1α staining, and the results are variable. For instance, Gilmore et al validated different methods to characterize hypoxia and found that HIF1α and Image IT probe spatial localizations correlate with each other [56]. On contrary, a study using patient tissue sections demonstrated that pimonidazole localization was confined to the central necrotic region in the center of the tissue, while HIF1α localization was not confined to the center [57].…”
Section: Discussionmentioning
confidence: 99%